Exploring the implementation of the TIME Home Learning programme and learning trajectories of 5- to 7-year-olds: Assessment tools for literacy and numeracy - von Blottnitz, Magali (Wordworks, Cape Town, 2025)
This brief presents and discusses two assessment tools that were developed/adapted for, and used in, the TIME longitudinal study (2022-2023): the Wordworks Early Literacy Assessment (WELA) and the Mathematics Early Learning Assessment (MELA), within the broader landscape of assessment tools available in South Africa for 5-7 year olds. The brief starts by reviewing which other tools existed for that age band at the time of the field study and makes the case for the adaptation of the WELA literacy tool, and the development of the MELA mathematics tool. It then explains briefly how the MELA was developed and how the WELA was adapted for the purpose of the study, including rounds of piloting and adjusting. Finally, it unpacks lessons learned from using them, and room for further development of those tools.
TIME Learning Brief 5
This is the fifth in a series of learning briefs that unpack learnings from the TIME longitudinal study. This brief focuses on the two assessment tools that were used in the study: the WELA (early literacy) and MELA (early mathematics). The brief presents the tools within the greater context of existing tools for that age band, explains briefly how they were developed or adapted, and what lessons were gained from using them.
Keywords: early literacy; early mathematics; numeracy; assessment tools; TIME; South Africa; Grade R; Grade 1; reading; writing; counting; WELA; MELA; Wordworks; RED INK